High Performance Liquid Chromatographic Determination of Azithromycin in Animal Feed - Ma, Suying; Shang, Xiaojun (Asian Journal of Chemistry, 2012)
A simple, precise, accurate and rapid high-performance liquid chromatography (HPLC) method was developed and validated for the determination of azithromycin in feed. The analyses were separated by the mobile phase 0.1 mol/L KH2PO4 (pH 6)-acetonitrile (70:30, v/v) with an SinoChoom ODS-BP C18 column (5 μm, 4.6 mm × 200 mm) at a flow rate of 1 mL/min, column temperature 35 ºC and detection wavelength 210 nm. A good linear relationship was obtained in the concentration range 0.5-50 mg/mL (r = 0.9993). The limit of quantification (LOQ) was 100 μg/g and the limit of detection (LOD) was 50 μg/g. Average recoveries ranged from 75.8 to 89.7 % in feed at the concentrations of 0.1-10 mg/g. Intra and interday relative standard deviations were less than 1.6 and 1.4 %, respectively. This HPLC method is simple, reproducible and accurate for determination of azithromycin in feed.